Life well-being and reasons for the termination of sport careers among Croatian elite athletes - Babic, V.; Bjelic, G.; Bosnar, K. (SportMont, 2019)
A sport career is, according to European Federation of Sport Psychology (FEPSAC, 2000), defined as a perennial engagement in sport activities directed at a high level of achievement of an individual and on his improvement in sport. It lasts from their entry until their exit from sport, and during their sport careers, athletes go through several developmental phases: initial phase, mastery phase, and exit phase, or postcareer (Wylleman, Alfermann, & Lavallee, 2004). The termination of a sport career can be a difficult and destructive process. Early and long-term identification with the role of an athlete at an exit from a sport can lead to confusion and can be a significant stressor. Problems with alcohol and drug abuse arise, as well as acute depression, eating disorders, identity disorders, confusion, a decline in self-confidence, and even suicide attempts (Wylleman et al., 2004). Results of early papers show that 70-80% of athletes are faced with various difficulties and traumas after retiring (Hallden, 1965; Mihoviloviæ, 1968; Haerle, 1975, according to Wylleman, Lavallee, & Alfermann, 1999; Wylleman et al., 2004). However, afterwards, it was established that this happens to a small number (13-19%) of athletes (Wylleman et al., 2004). Ceciæ Erpiè, Wylleman, and Zupanèiè (2004) have ascertained that quality of retirement depends on the voluntariness of career termination, the subjective evaluation of sport achievement, the intensity of sport identity, educational status and apparition of negative non-sports related transitions. Athletes` experiences at the elite level of sport are of crucial importance (Tshube & Feltz, 2015). The importance of social support and interpersonal relationships for adjustment